Pengaruh Shalat Tahajud Terhadap Kecemasan Pada Mahasiswa Tingkat Akhir - Riyandanie, Oktavia Gesti, Dr. Nisa Rachmah N.A., M.Si, Psi (2016)
Final year college students are required to create the essay that can cause anxiety. One way to reduce anxiety is salat tahajud therapy. The purpose of this study was to determine the effect of salat tahajud to anxiety's level of students who worked on the essay. Subjects in this study were two final year students were working on the essay, 21 years old, and had high anxiety's level. This research method using single case experimental design. Methods of data collection using a scale TMAS, interview, and behavioral checklist. Data were analyzed using chart analysis and statistic analysis Paired Sample Ttest. The results of the chart analysis showed that the two subjects a decrease in the level of anxiety. The results of the statistic analysis Paired Sample Ttest showed significance level of Pre-Post1 = 0.430 showed no decline, Pre-post2 = 0.156 showed no decline, Pre-Post3 = 0.052 showed no decline, Pre-Post4 = 0.135 showed no decline, Post1- post2 = 0.090 showed no decline, post2-Post3 = 0.386 showed no decline, Post3-Post4 = 0.330 showed no decline. However, from a mean value show a decrease, Pre mean: 39.0, Post1: 34.0, post2: 27.0, Post3: 20.5, Post4: 13.5. The conclusion of this study is to pray tahajud can reduce anxiety a fanal year students who worked on the essay. This is supported by the results of a behavior checklist and the interview of the subjects claimed to feel calmer after salat tahajud routine.